2022
DOI: 10.1021/acsabm.2c00126
|View full text |Cite
|
Sign up to set email alerts
|

Ibuprofen-Loaded Electrospun PCL/PEG Nanofibrous Membranes for Preventing Postoperative Abdominal Adhesion

Abstract: Electrospun nanofibrous membranes are a widely used physical barrier for reducing postoperative adhesion. However, these physical barriers could not prevent adhesion formation completely. Because a high-intensity inflammation occurs in the surgical area, the presence of relevant drugs to control such an inflammation is desperately needed. In this study, we fabricated an electrospun composite ibuprofen-loaded poly­(ethylene glycol) (PEG)/polycaprolactone (PCL) nanofibrous membrane (NFM) to prevent abdominal adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 68 publications
(206 reference statements)
0
12
0
Order By: Relevance
“…As a consequence, there were a greater number of round-shaped fibroblasts (poor proliferation) than spindle-shaped cells, and the cell shapes (as observed by phase contrast microscope ( Figure 8 : row 2) remained unchanged even after 72 h. Similar anti-adhesive ability of PCL based membranes are reported by the literature. 12
Figure 8.Fluorescence and Phase contrast images showing the cell behaviour on pure Poly (ε-caprolactone) (PCL) and Poly (ε-caprolactone)/Beeswax (PCL/BW) based membranes.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a consequence, there were a greater number of round-shaped fibroblasts (poor proliferation) than spindle-shaped cells, and the cell shapes (as observed by phase contrast microscope ( Figure 8 : row 2) remained unchanged even after 72 h. Similar anti-adhesive ability of PCL based membranes are reported by the literature. 12
Figure 8.Fluorescence and Phase contrast images showing the cell behaviour on pure Poly (ε-caprolactone) (PCL) and Poly (ε-caprolactone)/Beeswax (PCL/BW) based membranes.
…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, there were a greater number of round-shaped fibroblasts (poor proliferation) than spindle-shaped cells, and the cell shapes (as observed by phase contrast microscope (Figure 8: row 2) remained unchanged even after 72 h. Similar anti-adhesive ability of PCL based membranes are reported by the literature. 12…”
Section: Cellular Activity Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…[20] Research has demonstrated that 90% of patients experience abdominal adhesion, [46,86] which frequently results in subsequent surgeries, inadequate nutrition, complicated AWH, persistent and intense abdominal discomfort, intestinal blockages, female infertility, and fatality. [18,158,161,177] Abdominal adhesions persist as a vexing issue in clinical surgery [177] and have simulated the creation and fabrication of patches in an effort to tackle this problem. Anti-adhesive patches act as a mesh that shields the cellular signals between the caecum and the peritoneum, including charged proinflammatory cytokines (Figure 13A-iii).…”
Section: Anti-adhesionmentioning
confidence: 99%
“…There is a shift toward tissue engineering (TE) for the development of novel treatments . In the last decade, researchers have focused on fabricating multifaceted TE platforms to structurally and physiologically mimic the extracellular microenvironment which supports cells within native tissue. Such platforms include hydrogels, 3D printed scaffolds, electrospun fibers, microfluidic systems (organ-on-a-chip), and decellularized/recellularized tissues. In general, scaffold-based 3D culture systems used for the cultivation of hepatocytes are divided to three groups. One is hydrogel-based scaffolds, using natural-derived biomaterials such as collagen, alginate, gelatin, fibrin, and synthetic polymers such as poly lactic acid (PLA), poly glycolic acid (PGA), polycaprolactone (PCL), polyvinyl alcohol (PVA), and the combination of them .…”
Section: Introductionmentioning
confidence: 99%